MiR-92a Family: A Novel Diagnostic Biomarker and Potential Therapeutic Target in Human Cancers - Jiang, Min; Li, Xuelian; Quan, Xiaowei; Li, Xiaoying; Zhou, Baosen (Frontiers in Molecular Biosciences, 2019)
Purpose: This study tried to explore whether members of miR-92a family contribute to early diagnosis and prognosis for human cancers and how they work. Methods: Integrated meta-analysis retrieved from public repositories was employed to assess the clinical roles of miR-92a family for cancer diagnosis and prognosis. Expression level of miR-92a was detected by TCGA database and was confirmed by non-small-cell lung cancer (NSCLC) tissues. Targets of miR-92a were predicted using starbase, and validated by dual luciferase assay. Correlation between miR-92a and the target gene was assessed by linkedOmics while expression of target gene and its role in cancer prognosis were analyzed with UALCAN and Gepia. Results: We recognized miR-92a family could serve as a potential diagnostic biomarker with pooled sensitivity of 85% (95% CI: 81-88%) and specificity of 86% (95% CI: 83-90%). The overall HR was 2.26 (95% CI: 1.70-3.00) for high expression groups compared to low expression groups. Expression of miR-92a was identified to be upregulated in NSCLC, especially in lung squamous cell carcinoma (LUSC). Results from starbase and dual luciferase assay indicated RGS3 was a direct target of miR-92a. Statistical negative correlation was found for the expression of miR-92a and RGS3. In addition, expression of RGS3 was down-regulated in NSCLC and patients with the high expression had a poor prognosis (HR = 1.3) for LUSC patients. However, results was contrary for lung adenocarcinoma (HR = 0.7). Conclusion: This study revealed that miR-92a family could be ideal biomarkers for cancer diagnosis and prognosis, which might function through targeting RGS3.